The The Pragmatics of Provocation: A Forensic Linguistic Study of Religious Hate Speech in Contemporary Islamic Digital Discourse - Mu' aliyah Hi Asnawi (Journal of Pragmatics Research, 2026)
This study aims to analyze the forms, pragmatic functions, and provocative strategies of religion-based hate speech in contemporary digital Islamic discourse through a forensic linguistic approach. The study employed a qualitative method with a Critical Discourse Analysis (CDA) research design. The data consisted of 30 units of digital utterances collected from social media posts, online comments, and discussion forums containing indications of religion-based hate speech. Data were selected through purposive sampling based on the presence of negative labeling, collective accusations, calls for exclusion, delegitimization, and identity polarization. The analysis focused on speech acts, implicatures, presuppositions, politeness violations, perlocutionary effects, and rhetorical strategies of provocation. The findings reveal that online comments constituted the most dominant data source, accounting for 14 cases (46.67%). Representative speech acts were the most frequently identified category, comprising 11 cases (36.67%), indicating that provocation was predominantly constructed through claims, accusations, and negative evaluations directed at targeted groups. Among the pragmatic features, perlocutionary effects were the most prevalent (30.00%), while delegitimization emerged as the most common rhetorical strategy (23.33%). The study demonstrates that religious hate speech is not always expressed through overtly offensive or abusive language; rather, it often operates through implicit meanings, the construction of prejudice, and appeals for social exclusion.